Analisis Kelayakan Usaha Gula Kelapa di Kecamatan Kajang, Kabupaten Bulukumba - Evifirayanti Evifirayanti; Sulfiana Sulfiana; Suardi Bakri (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to identify the factors influencing the success of coconut sugar enterprises in Kajang District, Bulukumba Regency; analyze the income generated from coconut sugar production; and assess the financial feasibility of coconut sugar businesses in the region. The research employs a mixed-methods approach, combining both qualitative and quantitative methods. This approach was selected to describe the actual conditions of coconut sugar enterprises in the field and to analyze measurable relationships between variables affecting income and business feasibility. The qualitative method was used to explain the socioeconomic characteristics of coconut sugar producers and the conditions of their enterprises, while the quantitative method was used to calculate income, profit, and several financial feasibility indicators Revenue Cost (R/C) Ratio, Benefit Cost (B/C) Ratio, Gross Margin, Net Profit Margin, Return on Investment (ROI), Net Present Value (NPV), and Break-Even Point (BEP).The results show that factors influencing the success of coconut sugar businesses include age, experience, education level, land area, number of dependents, and climatic conditions. Based on the financial analysis, the coconut sugar business is considered feasible to develop. The R/C Ratio value of 2.50 indicates that every Rp1 of cost generates Rp2.50 in revenue. The B/C Ratio of 1.50 signifies that the net profit obtained is 1.5 times the cost incurred. A Gross Margin of 76% reflects efficient use of variable costs, while a Net Profit Margin of 60% indicates that more than half of the total revenue becomes net profit.